Investigating the Structural Model of Whistle Blowing System on Government Procurement Fraud: Examining Mediating Effect of Investigative Audit - Zahra, Femilia; Abdullah, Muhammad Ikbal; Din, Muhammad; Fadli, Mohammad; Besar, Hairul Azrin Haji; Ali, Jati Kasuma (International Journal of Economics and Financial Issues, 2024)
This study aims to develop a fraud disclosure model in government procurement in Indonesia through a whistle blowing system with an investigative audit as a mediator. Disclosure of fraud is the result of an investigative audit. The effectiveness of the implementation of investigative audit procedures will be achieved if the auditor has the ability to carry out each stage in the audit standard. To maximize the performance of investigative audits, a system is needed to uncover fraud. The whistleblowing system is expected to be an effective tool to reveal fraud in government procurement. The research was conducted by distributing questionnaires to respondents electronically by sending a google form link containing a list of questions to auditors at the Supreme Audit Agency (BPK) and internal auditors at the Financial and Development Supervisory Agency (BPKP) throughout Indonesia. The results of the study found that the use of a whistle blowing system could increase the effectiveness of investigative audits on government procurement. Another finding is that investigative audits can reduce the disclosure of government procurement fraud. The effectiveness of the whistle blowing system in reducing the level of disclosure of government procurement fraud does not occur directly, but must be mediated by a good investigative audit. The results of this study indicate that the reporting of government procurement fraud cases on the whistle blowing system must be followed up with a thorough investigative audit so that disclosures of government procurement fraud cases can be traced better. Additional analysis in this study shows that although the functions of external auditors and internal auditors are different, the level and type of disclosure of government procurement fraud do not differ.